Linguistic and Stylistic Markers of Influence in the Essayistic Text: A Linguophilosophic Aspect - Колкутіна, Вікторія Вікторівна; Колкутіна, В. В.; Колкутина, Виктория Викторовна; Kolkutina, Viktoriia V.; Орєхова, Лариса Іванівна; Орєхова, Л. І.; Орехова, Лариса Ивановна; Oriekhova, Larysa I.; Orekhova, Larysa; Гремалюк, Тетяна Василівна; Гремалюк, Т. В.; Гремалюк, Татьяна Васильевна; et al. (IJCSNS, 2022)
The article explores linguo-stylistic influence markers in essayistic texts. The novelty of this investigation is provided by its perspective. Essayism is looked at as a style of thinking and writing and studied as a holistic philosophical and cultural phenomenon, as a revalent form of comprehension of reality that features non-lasting author’s judgements and enhancement of the author’s voice in the text. Based on the texts by V. Rosanov, G.K. Chesterton, and D. Dontsov, the remarkable English, Russian, and Ukrainian essay-writers of the first party of the 20th century, the article tracks the typical ontological-and-existentialist correlation at the content, stylistic, and semantic levels. It is observed in terms of the ideas presented in the texts of these publicists and the lexico-stylistic markers of the influence on the reader that enable these ideas to implement. The explored poetic syntax, key lexemes, dialogueness, intonational melodics, specific language, free associations, aphoristic nature, verbalization of emotions and feeling in the psycholinguistic form of their expression, stress, heroic elevation, metaphors and evaluative linguistic units in the ontological-and-existentialist aspects contribute to extremely delicate and demanding nature of the essayistic style. They create a “lacework” of unpredictable properties, intellectual illumination, unexpected similarity, metaphorical freshness, sudden discoveries, unmotivated unities.

У статті досліджуються лінгвостилістичні маркери впливу в есеїстичних текстах. Новизна цього розслідування забезпечується його перспективністю. Есеїзм розглядається як стиль мислення та письма і вивчається як цілісний філософсько-культурний феномен, як актуальна форма осягнення дійсності, що містить нетривалі авторські судження та посилення авторського голосу в тексті. На основі текстів В. Розанова, Г.К. Честертона та Д. Донцова, видатних англійських, російських та українських есеїстів першої половини ХХ ст., у статті простежується типове онтологічно-екзистенціалістичне співвідношення на змістовному, стилістичному та семантичному рівнях. Це спостерігається з точки зору ідей, викладених у текстах цих публіцистів, і лексико-стилістичних маркерів впливу на читача, що дають змогу цим ідеям реалізуватися. Досліджені поетичний синтаксис, ключові лексеми, діалогічність, інтонаційна мелодика, специфічна мова, вільні асоціації, афористичність, вербалізація емоцій і почуттів у психолінгвістичній формі їх вираження, наголос, героїчне піднесення, метафори та оцінні мовні одиниці в онтологічно- екзистенціалістичних аспектах сприяють надзвичайно делікатному й вимогливому характеру есеїстичного стилю. Вони створюють «мереживо» з непередбачуваних властивостей, інтелектуального освітлення, несподіваної схожості, метафоричної свіжості, раптових відкриттів, невмотивованих єдностей.
Kolkutina V. Linguistic and Stylistic Markers of Influence in the Essayistic Text: A Linguophilosophic Aspect / V. Kolkutina, L. Orekhova, T. Gremaliuk, et al. // International journal of computer science and network security. - Vol. 22. - Iss. 5 IJCSNS, 2022. - Р. 163-167.
Keywords: philosophy; language; stylistics; essayism; text; філософія; мова; стилістика; есеїстика; текст; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Philosophy subjects; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics::Linguistic subjects